Effects of Natural Polyphenols on Oxidative Stress-Mediated Blood–Brain Barrier Dysfunction - Kim, Yeonjae; Cho, A. Yeon; Kim, Hong Cheol; Ryu, Dajung; Jo, Sangmee Ahn; Jung, Yi Sook (Antioxidants, 2022)
The blood–brain barrier (BBB), which consists mainly of brain microvascular endothelial cells and astrocytes connected by tight junctions (TJs) and adhesion molecules (AMs), maintains the homeostatic balance between brain parenchyma and extracellular fluid. Accumulating evidence shows that BBB dysfunction is a common feature of neurodegenerative diseases, including stroke, traumatic brain injury, and Alzheimer’s disease. Among the various pathological pathways of BBB dysfunction, reactive oxygen species (ROS) are known to play a key role in inducing BBB disruption mediated via TJ modification, AM induction, cytoskeletal reorganization, and matrix metalloproteinase activation. Thus, antioxidants have been suggested to exert beneficial effects on BBB dysfunction-associated brain diseases. In this review, we summarized the sources of ROS production in multiple cells that constitute or surround the BBB, such as BBB endothelial cells, astrocytes, microglia, and neutrophils. We also reviewed various pathological mechanisms by which BBB disruption is caused by ROS in these cells. Finally, we summarized the effects of various natural polyphenols on BBB dysfunction to suggest a therapeutic strategy for BBB disruption-related brain diseases.
Keywords: Blood–brain barrier (BBB); Natural polyphenols; Oxidative stress; Reactive oxygen species (ROS)